2000
DOI: 10.1046/j.1471-4159.2000.0752492.x
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Potentiation of Acetylcholine Effects on Neuronal Nicotinic Receptors by Acetylcholinesterase‐Inhibiting Drugs

Abstract: Abstract:The effects of the acetylcholinesterase inhibitors physostigmine and tacrine on ␣4␤2 and ␣4␤4 subtypes of neuronal nicotinic acetylcholine (ACh) receptors, expressed in Xenopus laevis oocytes, have been investigated. In voltage-clamp experiments low concentrations of physostigmine and tacrine potentiate ion currents induced by low concentrations of ACh, whereas at high concentrations they inhibit ACh-induced ion currents. These dual effects result in bell-shaped concentrationeffect curves. Physostigmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Similar effects were previously reported for cholinergic drugs at α4β2 nAChRs. 23,26 The AT-1001 concentration-inhibition curve at α3β4 nAChR ( Figure 3B) therefore has a complex shape that is better fitted by a two-site equation (Equation 1) that was initially developed to take into account the bell-shaped inhibition curve observed with some antagonists at the α3β4 nAChR. 22 This equation was subsequently elaborated further to take into account the possibility that the test compound might also act as an open-channel blocker.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were previously reported for cholinergic drugs at α4β2 nAChRs. 23,26 The AT-1001 concentration-inhibition curve at α3β4 nAChR ( Figure 3B) therefore has a complex shape that is better fitted by a two-site equation (Equation 1) that was initially developed to take into account the bell-shaped inhibition curve observed with some antagonists at the α3β4 nAChR. 22 This equation was subsequently elaborated further to take into account the possibility that the test compound might also act as an open-channel blocker.…”
Section: Discussionmentioning
confidence: 99%
“…Together, the whole-cell and single-channel findings are suggestive of low potency and/or low efficacy of physostigmine on the nAChR. Physostigmine-mediated potentiation of currents elicited by low doses of ACh has been shown for neuronal (Zwart et al, 2000) as well as muscle-type nicotinic receptors (Svobodova et al, 2006).…”
mentioning
confidence: 91%
“…The plant-derived APLs physostigmine and galantamine were originally identified as acetylcholinesterase inhibitors, leading to their use in symptomatic treatment of neurological disorders involving memory deficits (Davis et al, 1978;van Dyck et al, 2000). Later work showed that the drugs also act on the nAChR where they potentiate currents elicited by low concentrations of nicotinic agonists; cause direct activation of the channel; and, at higher doses, block channel activity (Albuquerque et al, 1984;Okonjo et al, 1991;Zwart et al, 2000).…”
mentioning
confidence: 99%
See 2 more Smart Citations